Pengembangan Media Audio Visual Melalui Youtube Tentang Cara Menjaga Personal Hygiene Saat Menstruasi di Smpn 18 Surakarta - Putri Zakia Ulfa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Personal hygiene is the improvement of health through the implementation of hygiene measures carried out during menstruation with the aim of maintaining individual cleanliness and health so as to obtain physical, psychological well-being and increase the degree of welfare. The purpose of this study is to find out how the procedure for developing audio-visual media with youtube and to find out the feasibility of audio-visual media through assessments from experts and respondents. This research is included in Research and Development (R&D) with reference to the research model from Borg & Gall. The results of this study show that the average value of the validation test for material experts is 95% with the category of very feasible and 95% of media experts with the category of very feasible. The feasibility test of the product with student validation was 86.2% with the category of very feasible. The conclusion that this audio-visual media received a good response to be used as an educational medium on how to maintain personal hygiene during menstruation.